The Influence of Chatbot Usage and Product Recommendation Features on Customer Satisfaction in Shopee E-Commerce - Sirait, Nadia Theresia; Saputra, Hendra (Economic: Journal Economic and Business, 2025)
This study aims to determine the effect of Chatbot and Product Recommendation Features in increasing customer satisfaction in Shopee E-Commerce. This study uses a quantitative approach with a descriptive method. Data were obtained by distributing questionnaires to 97 respondents who were active students at Medan State University class of 2021 who had used Shopee. The data analysis technique used was multiple linear regression. The results of the study showed that Chatbot had a positive and significant effect on Customer Satisfaction, as did the Product Recommendation Feature which showed a positive effect. Simultaneously, both variables had a significant effect on Customer Satisfaction. This study provides implications that service quality and a relevant and trusted recommendation system can increase customer satisfaction on e-commerce platforms.